Concerning Two-Level Structure of Potential Epidemic Hazard of the Mass Events with International Participation - G. G. Onishchenko; M. A. Patyashina; S. K. Udovichenko; A. V. Toporkov; V. P. Toporkov; V. V. Kutyrev (Проблемы особо опасных инфекций, 2015)
The paper discusses epidemiological environment of particular countries and parts of the world viewed as potential platforms for mass events with international participation. It is established that the most unfavorable in this respect are Asian countries, primarily South-Eastern Asia ones, and African ones, from where the majority of well-known pandemics and epidemics have originated. Specified are the factors which are significant for spread of infectious diseases that can trigger emergency situation of sanitary epidemiological character of international concern. They are tourism and migration, trade and economic affairs, natural and anthropogenic disasters. The concept - “potential epidemic hazard of mass events with international participation” - is defined. It is demonstrated that its structure comprises two levels: the natural background of endemic and imported as related to mass event region epidemiological hazards, and epidemiological hazards imposed by the event itself. Outlined is a step-by-step algorithm for assessment of “potential epidemic hazard” of mass events with international participation allowing for adjustment of measures for the provision of sanitary and epidemiological welfare of the population.